Esophageal replacement by colon interposition with microvascular surgery for patients with thoracic esophageal cancer: the utility of superdrainage. Issue 1 (6th March 2012) - Saeki, H.; Morita, M.; Harada, N.; Egashira, A.; Oki, E.; Uchiyama, H.; Ohga, T.; Kakeji, Y.; Sakaguchi, Y.; Maehara, Y.
Summary Replacing the thoracic esophagus with the colon is one mode of reconstruction after esophagectomy for esophageal cancer. There is, however, a high incidence of postoperative necrosis of the transposed colon. This study evaluated the outcomes of colon interposition with the routine use of superdrainage by microvascular surgery. Twenty‐one patients underwent colon interposition from 2004 to 2009. The strategy for colon interposition was to: (i) use the right hemicolon; (ii) reconstruct via the subcutaneous route; (iii) perform a microvascular venous anastomosis for all patients; and (iv) perform a microvascular arterial anastomosis when the arterial blood flow was insufficient. The clinicopathologic features, surgical findings, and outcomes were investigated. The colon was used because of a previous gastrectomy in 18 patients (85.7%) and synchronous gastric cancer in three patients (14.3%). Eight patients (38.1%) underwent preoperative chemoradiotherapy including three (14.3%) treated with definitive chemoradiotherapy. Seven patients (33.3%) underwent microvascular arterial anastomosis to supplement the right colon blood supply. Pneumonia occurred in four patients (19.0%). Anastomotic leakage was observed in five patients (23.8%); however, no colon necrosis was observed. The 3‐year and 5‐year overall survival rates were both 50.6%. Colon interposition with superdrainage results in successful treatment outcomes. This technique is one option for colon interposition employing the right hemicolon.